Analisis faktor-faktor yang mempengaruhi Pendapatan Asli Daerah (PAD) pada kabupaten/ kota Provinsi Jawa Tengah - Rina Hidayanti; Aprilia Whetyningtyas; Zamrud Mirah Delima (Journal of Accounting and Digital Finance, 2025)
This study aims to examine the effect of Regional Taxes, Regional Levies, Results of Separated Regional Asset Management, Other Legitimate Regional Income, and Population on Regional Original Income in Regencies/Cities of Central Java Province for the 2018-2023 Period. This study uses quantitative methods and secondary data. The sampling technique uses the census method based on data from the 2018-2023 Budget Realization Report and Information obtained from the Central Statistics Agency (BPS), with a sample size of 210 after analyzing 155 samples for outliers. This research method is multiple linear regression analysis. The results of this study indicate that regional taxes, regional levies, results of separate regional asset management, and other legitimate regional income have a positive effect on regional original income (PAD). In contrast, population negatively affects regional original income (PAD).